2017
DOI: 10.1093/jisesa/iex017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Four ATP-Binding Cassette Transporter Genes in Cnaphalocrocis medinalis and Their Expression in Response to Insecticide Treatment

Abstract: The ATP-binding cassette (ABC) transporters belong to a superfamily of genes involved in the transport of specific molecules across lipid membranes, as well as insecticide resistance, present in all living organisms. In this study, we combined the Cnaphalocrocis medinals transcriptome database with a bioinformatics approach to identify four C. medinals ABCs (CmABCs), including CmABCG1, CmABCG4, CmABCC2 and CmABCC3. Tissue expression analysis showed that these genes had a tissue-specific expression pattern. CmA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…The results of the present study indicate that the ABCG transporter in BPH shows varying responses to different levels of thiamethoxam, abamectin, and cyantraniliprole stress. Similar results have been observed in Anopheles sinensis [29], Bactrocera dorsalis [22], and Cnaphalocrocis medinalis [41]. Although these findings do not directly suggest that the ABCG transporter is involved in the development of insect resistance, our results provide insight into the function of the ABCG transporter.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study indicate that the ABCG transporter in BPH shows varying responses to different levels of thiamethoxam, abamectin, and cyantraniliprole stress. Similar results have been observed in Anopheles sinensis [29], Bactrocera dorsalis [22], and Cnaphalocrocis medinalis [41]. Although these findings do not directly suggest that the ABCG transporter is involved in the development of insect resistance, our results provide insight into the function of the ABCG transporter.…”
Section: Discussionsupporting
confidence: 90%
“…Plant-derived EOs are also capable of inhibiting GABA receptors present in insects, which can suspend GABA from binding with GABArs (GABA receptors) in extrasynaptic synaptic membranes [ 64 , 65 , 66 ] ( Figure 1 ). Furthermore, phytochemical metabolites from plant-derived EOs can inhibit or interfere the activities of enzymes associated with the metabolism of xenobiotics and respiration of insects like CarEs, chitin, cytochrome P450s, ATP-binding cassette transporters and GSTs [ 67 , 68 , 69 ].…”
Section: Pesticidal and Fungicidal Action Mechanisms Of Plant-derived Essential Oilsmentioning
confidence: 99%
“…(2014), found that AnstABCG4 expression is up-regulated in permethrin-treated Anopheles stephensi . Here, we identified the up-regulated expression of ABC transporters in insecticide-resistant G. pyloali s. Likewise, a recent study revealed that the transcription of CmABCG1 , CmABCG4 and CmABCC2 were significantly induced by chlorpyrifos in C. medinalis (Yu et al ., 2017). In this study, the identification of transcripts in these classes of ABC transporters promotes further studies into their involvement in insecticide resistance.…”
Section: Discussionmentioning
confidence: 99%